1999
DOI: 10.1002/(sici)1097-4644(19990901)74:3<458::aid-jcb13>3.3.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

Only a small portion of the cytoplasmic progesterone receptor is associated with Hsp90 in vivo

Abstract: In cell extracts all of the nonliganded steroid receptor molecules are found as an oligomeric complex with Hsp90 and other proteins. In previous studies we have shown that Wild-type Hsp90 and progesterone receptor (PR) are located in different cell compartments (Tuohimaa et al. [1993] Proc. Natl. Acad. Sci. USA 90:5848-5852). In the present work we studied whether PR and Hsp90 can efficiently associate provided they are present in the same cell compartment. The association of Hsp90 with PR in vivo was studied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2001
2001
2001
2001

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Our previous immunohistochemical studies, performed with antibodies that distinguish the oligomeric and dissociated forms of the receptors, are also in concert with this interpretation (Passinen et al 1999). It has been demonstrated that recombinant Hsp90, artificially targeted to the nucleus by a heterologous NLS, cotransported a fraction of cytoplasmic steroid receptor mutants into the nucleus (Kang et al 1994;Passinen et al 1999). Kang et al (1994) reasoned that if NLS-Hsp90 could transport the cytoplasmic receptors into the nucleus, intact steroid receptors should reciprocally cotransport cytoplasmic Hsp90 to the nucleus.…”
Section: Discussionmentioning
confidence: 90%
“…Our previous immunohistochemical studies, performed with antibodies that distinguish the oligomeric and dissociated forms of the receptors, are also in concert with this interpretation (Passinen et al 1999). It has been demonstrated that recombinant Hsp90, artificially targeted to the nucleus by a heterologous NLS, cotransported a fraction of cytoplasmic steroid receptor mutants into the nucleus (Kang et al 1994;Passinen et al 1999). Kang et al (1994) reasoned that if NLS-Hsp90 could transport the cytoplasmic receptors into the nucleus, intact steroid receptors should reciprocally cotransport cytoplasmic Hsp90 to the nucleus.…”
Section: Discussionmentioning
confidence: 90%